Effectiveness of Amiodarone in Preventing the Occurrence of Reperfusion Ventricular Fibrillation After the Release of Aortic Cross-Clamp in Open-Heart Surgery Patients: A Meta-Analysis - He, Li-min; Zhang, An; Xiong, Bin (Frontiers in Cardiovascular Medicine, 2022)
Objective To evaluate the efficiency of amiodarone in preventing the occurrence of reperfusion ventricular fibrillation (RVF) after aortic cross-clamp (ACC) release in patients undergoing open-heart surgery. Methods We searched the Web of Science, Cochrane Library, EMBASE, and PubMed databases through January 2021 for relevant studies addressing the efficacy of amiodarone in preventing RVF after ACC release in patients undergoing cardiac surgery. A complete statistical analysis was performed using RevMan 5.3. Risk ratios (RRs) and 95% confidence intervals (CIs) were calculated to express the results of dichotomous outcomes using random or fixed-effect models. The chi-square test and I2 test were used to calculate heterogeneity. Results Seven studies (856 enrolled patients; 311 in the amiodarone group, 268 in the lidocaine group, and 277 in the placebo group) were selected for the meta-analysis. The incidence of RVF was significantly decreased in the amiodarone group compared to the placebo group (RR = 0.69, 95%CI: 0.50–0.94, P = 0.02). However, amiodarone and lidocaine did not confer any significant difference (RR = 0.98, 95%CI: 0.61–1.59, P = 0.94). The percentage of patients requiring electric defibrillation counter shocks (DCSs) did not confer any significant difference between patients administered amiodarone and lidocaine or placebo (RR = 1.58, 95%CI: 0.29–8.74, P = 0.60; RR = 0.55, 95%CI: 0.27–1.10, P = 0.09; respectively). Conclusions Amiodarone is more effective than a placebo in preventing RVF after ACC release in cardiac surgery. However, the amiodarone group required the same number of electrical DCSs to terminate RVF as the lidocaine or placebo groups.